Chemical Structure and Morphology of Dorsal Root Ganglion Neurons from Naive and Inflamed Mice - Barabas, Marie E. (J Biol Chem, 2014)
Fourier transform infrared spectromicroscopy provides label-free imaging to detect the spatial distribution of the characteristic functional groups in proteins, lipids, phosphates, and carbohydrates simultaneously in individual DRG neurons. We have identified ring-shaped distributions of lipid and/or carbohydrate enrichment in subpopulations of neurons which has never before been reported. These distributions are ring-shaped within the cytoplasm and are likely representative of the endoplasmic reticulum. The prevalence of chemical ring subtypes differs between large- and small-diameter neurons. Peripheral inflammation increased the relative lipid content specifically in small-diameter neurons, many of which are nociceptive. Because many small-diameter neurons express an ion channel involved in inflammatory pain, transient receptor potential ankyrin 1 (TRPA1), we asked whether this increase in lipid content occurs in TRPA1-deficient (knock-out) neurons. No statistically significant change in lipid content occurred in TRPA1-deficient neurons, indicating that the inflammation-mediated increase in lipid content is largely dependent on TRPA1. Because TRPA1 is known to mediate mechanical and cold sensitization that accompanies peripheral inflammation, our findings may have important implications for a potential role of lipids in inflammatory pain.